Exploring the inhibitory potential of in silico-designed small peptides on Helicobacter pylori Hp0231 (DsbK), a periplasmic oxidoreductase involved in disulfide bond formation - Roszczenko-Jasińska, Paula; Giełdoń, Artur; Mazur, Dominika; Spodzieja, Marta; Plichta, Maciej; Czaplewski, Cezary; Bal, Wojciech; Jagusztyn-Krynicka, Elzbieta K.; Bartosik, Dariusz (Frontiers in Molecular Biosciences, 2024)
Helicobacter pylori is a bacterium that colonizes the gastric epithelium, which affects millions of people worldwide. H. pylori infection can lead to various gastrointestinal diseases, including gastric adenocarcinoma and mucosa-associated lymphoid tissue lymphoma. Conventional antibiotic therapies face challenges due to increasing antibiotic resistance and patient non-compliance, necessitating the exploration of alternative treatment approaches. In this study, we focused on Hp0231 (DsbK), an essential component of the H. pylori Dsb (disulfide bond) oxidative pathway, and investigated peptidebased inhibition as a potential therapeutic strategy. Three inhibitory peptides designed by computational modeling were evaluated for their effectiveness using a time-resolved fluorescence assay. We also examined the binding affinity between Hp0231 and the peptides. Our findings demonstrate that in silico-designed synthetic peptides can effectively inhibit Hp0231-mediated peptide oxidation. Targeting Hp0231 oxidase activity could attenuate H. pylori virulence without compromising bacterial viability. Therefore, peptide-based inhibitors of Hp0231 could be candidates for the development of new targeted strategy, which does not influence the composition of the natural human microbiome, but deprive the bacterium of its pathogenic properties.